Pathomorphological changes in the larvae cells of blood-suckıng mosquitoes (Aedes caspius Pallas, 1771) affected by parasitizing microsporidium Amblyospora (=Thelohania) opacita Kudo, 1922 - Nasirov, A.; Gasimov, E.; Ibrahimova, N.; Rzayev, F. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
Microsporidia are highly specialized obligate intracellular parasites. They affect various tissues of most animal groups. In Azerbaijan, 29 species and forms of microsporidia were recorded. Of these, 10 species (Amblyospora minuta, Pleistophora obesa, Thelohania opacita, Th. opacita caspius, Th. vexans, Stempellia captshagaica, St. magna, Nosema caspius, Nosema sp., Culicosporella sp.) were found in four species of blood-sucking mosquitos (Culix pipiens pipiens, Aedes vexans, A. caspius, Culex theileri). The collected larvae were identified using the key of Gutsevich et al. (1970). In the laboratory, the mosquito larvae were examined against a dark background under the microscope MBS-9 to distinguish individuals infected with microsporidia. Smears were stained with azure-eosin. Histological slices were prepared according to the Volkova and Yeletskiy method (1971); pathological changes in host tissues were identified using the electron microscope JEM 1400. In the course of our research conducted in 2017–2018 on the Absheron peninsula (Azerbaijan), the life stages of the microsporidium Amblyospora (=Thelohania) opacita Kudo, 1922 were found in the larvae of Aedes caspius Pallas, 1771. Examination of the infected host cell ultrastructure revealed the following changes: rough endoplasmic reticulum and mitochondria concentration around the parasite, an increase of cytoplasm volume, initiation of cell hypertrophy, disappearance of fat, protein granules and rough endoplasmic reticulum at later development stages, a decrease in the number of ribosomes in the cytoplasm and their simultaneous increase around the periphery of the nucleus, mitochondria degradation. These changes cause a delay in the larva development. Microsporidiosis affects the whole mosquito life cycle. The effect of microsporidia on the host organism manifests itself in the delayed larvae development and, in some cases, their early death. First of all, the lipid granules disappear supposedly because of the intensification of the host's aerobic metabolism to compensate for the energy loss caused by the developing parasites.